Research on the factors influencing the width of hydraulic fractures through layers - Yunpei Liang; Mao Wang; Yongjiang Luo; Tao Rui; Xing Wang; Yu Meng (Journal of Petroleum Exploration and Production Technology, 2024)
Abstract The method of segmented hydraulic fracturing in the coal seam roof has proven to be an efficient technique for coalbed methane exploitation. However, the behavior of hydraulic fractures in multilayer formations with significant differences in mechanical properties is still unclear. This paper studied the variation in hydraulic fracture width at the coal-rock interface by employing experimental method with a true triaxial hydraulic fracturing experimental system and numerical simulation method. Results revealed that the hydraulic fracture more likely to expanded along the coal-rock interface instead of break through it with the small horizontal stress difference and low flow rate injection condition. And improving the injection flow rate lager than a critical value, the hydraulic fracture tends to break through the coal-rock interface. Hydraulic fractures in both mudstone and coal beds exhibited a trend of increasing and then decreasing of fracture width at the interface. Since the strength of the coal seam was lower compared to that of the mudstone, maintaining high pressure was no longer necessary when the hydraulic fracture crossed the interface and entered the coal seam, leading to a reduction in fracture width within the mudstone. During the later stages of fracturing, the entry of proppant into the coal seam became challenging, resulting in a phenomenon characterized by excessive fluid but insufficient sand. The time required for the fracture width to traverse the proppant was found to be inversely proportional to the difference in horizontal ground stress and the flow rate of the fracturing fluid. And it was directly proportional to the modulus of elasticity, permeability of the coal seam, and interface strength. The interface strength has the greatest influence on the width of hydraulic fractures. In conclusion, this study provides valuable insights into the behavior of hydraulic fractures in multilayer formations with varying mechanical properties. The findings contribute to a better understanding of the factors affecting hydraulic fracture width within coal seams, which can ultimately enhance the efficiency of coalbed methane exploitation.